Prepectoral and Retropectoral Breast-implant-Associated Anaplastic Large-cell Lymphoma - Ziegler-Rodriguez, G (2024)
Summary: Breast-implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a non-Hodgkin lymphoma that arises in the space between the surface of a breast implant and the fibrous capsule that grows around the implant. Since its first description 20 years ago, almost 1000 cases of BIA-ALCL have been diagnosed worldwide. Nowadays, guidelines describe the diagnosis, staging, and treatment of this disease. We present the first two cases diagnosed and treated in Peru, demonstrating a wide range of aggressiveness of BIA-ALCL. © Plastic and Reconstructive Surgery - Global Open.All rights reserved.